Sistem Informasi Bantuan Keuangan Pada Dinas Keuangan Aceh - Munandar, Teuku Arib; Imilda; Ismail (Journal Innovations Computer Science, 2023)
Financial assistance information system is a crucial data processing activity within the Aceh Department of Finance, aimed at obtaining well-directed and easily accessible information regarding financial assistance reports. This research focuses on the design of the Financial Assistance Information System within the Aceh Department of Finance, utilizing the CodeIgniter framework along with programming languages such as HTML, PHP, CSS, JSON, AJAX, and MySQL as the supporting database. The purpose of this study is to understand and design the Financial Assistance Information System within the Aceh Department of Finance using the CodeIgniter framework and programming languages like HTML, PHP, CSS, JSON, AJAX, and MySQL as the supporting database. Data collection for this report was obtained through two methods: literature review involving relevant library books and other scholarly works, and field study involving interviews and direct observations related to this research. The financial assistance information system is administered by a finance department administrative staff responsible for recording and inputting financial assistance report data. The research findings conclude that the Financial Assistance Information System at the Aceh Department of Finance adheres to procedures, employing the CodeIgniter framework and programming languages such as HTML, PHP, CSS, JSON, AJAX, and MySQL as the supporting database.